Occupational exposure to paint solvents and particulate material in car repair shops - Lepera, José Salvador [UNESP]; Colacioppo, Sergio (My University, 2005)
Aims: We evaluated solvents and total particulates exposures in auto body repair shops together with a search of painter's related complaints. Methods: 26 painters exposures were evaluated by pumped personal sampling; solvents were retained in charcoal sorbent tubes and the particulates in PVC filters. Painter's personal habits and their work characteristics were obtained through a questionnaire, applied in a private interview. For the symptoms the Q16 questionnaire was used, added of questions about complaints during the painting. Results: High exposures were detected during spray painting. For solvents, the TLV-STEL adjusted for the mixtures was surpassed in six evaluations. However, as repaint is a short-term operation, it makes the average concentrations weighed for the work shift lower than the TLV-TWA adjusted for the mixtures. Total particulate concentrations had surpassed the TLV-TWA in four of the evaluations. Symptoms frequency in the Q16 questionnaire was higher for painters than for the controls (Mann-Whitney test U=193; p=0.008), and they showed positive correlations with the age (Spearman r=0.354, t=1.85, p=0.076), the number of years in the profession (Spearman r=0.433, t=2.35, p=0.027) and the alcoholic beverage consumption (Spearman r=0.457, t=2.516, p=0.019). Conclusions: The painting work done at car repair shops can result in high solvent and particulate exposures, although they are short-term operations. Their acute and chronic effects for the painters do not have been clearly evidenced in the present study, continuing deserving multidisciplinary attention.
Keywords: Automotive repaint; Occupational exposure; Particulate matter; Solvents; charcoal; solvent; sorbent; thinner; adult; alcohol consumption; alcoholic beverage; car; conference paper; controlled study; filter; habit; human; interview; occupation; occupational exposure; painter; painting; particulate matter; questionnaire; rank sum test; shift worker; work; workplace